EVALUATION OF ANTIMICROBIAL ACTIVITY OF THE LICHENS PHYSCIA AIPOLIA, XANTHORIA PARIETINA, USNEA FLORIDA, USNEA SUBFLORIDANA AND MELANOHALEA EXASPERATA - (:unkn) unknown (STATE NATURAL HISTORY MUSEUM NAS UKRAINE, 2016)
The present study aimed to evaluate the antimicrobial activity of methanol and chloroform extracts of five lichen species, Melanohalea exasperata, Physcia aipolia,Uslwallorida, U. sithfloridana and Xanthoria parietina. Antimicrobial activity in culture assays of these foliose and fru ticose lichen extracts were examined against two Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli), two Gram-positive bacteria (Enterococcus faecalis and Staphylococcus aureus), and the yeast Candida albicans using the paper disc method through determination of minimal inhibitory concentrations (MICs). The obtained results indicated the existence of different levels of antibiotic substances in the chloroform and the methanol extracts of the examined lichen species. The chloroform extracts of Usnea subfloridana showed the highest activity against Escherichia coli and Pseudomonas aeruginosa while the methanol extracts of this species were not active against these microorganisms. The chloroform extracts of the examined species exhibited more significant antimicrobial activity than the methanol extracts. None of the species were active against Enterococcus faecalis and Staphylococcus aureus. Most of the lichen extracts indicated a moderate antifungal activity against Candida albicans, except for Physcia aipolia, which was not active.
Keywords: antimicrobial activity; lichen; MIC; ANTIFUNGAL ACTIVITY; USNIC ACID; EXTRACTS; ANTIBACTERIAL; METABOLITES; CELLS